Changes in the Macro-, Mezo-, and Microelement Contents of Maize Hybrids in Relation to the Level of Nutrient Supply - Jakab, Péter (Acta Agraria Debreceniensis, 2003)
n my research, I measured the effect of NPK fertilisation on the macro- meso- and microelements content of maize hybrids in 2001. The experiment was set in the demonstration garden of the Department of Crop Production and Applied Ecology in the Agricultural Centre, at the University in Debrecen. The soil of the experiment is calcerous chernozem soil. Five fertilisation steps were applied. Besides the control the smallest rate was 40 kg N; 25 kg P2O5; 30 kg K2O of active ingredients. The largest rate was five times more than the smallest one: 200 kg N; 125 kg P2O5; 150 kg K2O, which is equal to 475 kg mixed active ingredients. The NPK treatment significantly influenced the macrolement content in several cases. The N content was the lowest in the control treatment. Compared to this the fertiliser treatments significantly increased the N content of hybrids. However the highest amounts of potassium and phosphorus could be measured in the control and the lowest amounts could be measured at the N 200+PK kg/ha treatment. The Ca content of hybrids was the highest in the N 120+PK kg/ha treatment, while their Mg and Zn content was the highest in the control treatment. The lowest amounts were weighed in the N 200+PK kg/ha treatments, that in several cases resulted in statistically proved decreasement compared to the control or the lower fertilizer doses. Considering the two mesoelements and Zn the most favourable results were obtained in the case of the Norma SC and DK 366 SC hybrids. Summing up what has been said moderate amounts of fertiliser doses (N 40-120+PK kg/ha) had a favourable influence on the micro- and macroelement content of hybrids.